Self-esteem and Academic Self Concept: A Comparison of Government and Private Schools in Quetta - Azam, Maham; Saleem, Ghina; Ali, Muhammad (Annals of Human and Social Sciences, 2025)
The study investigated the differences in academic self-concept and self-esteem of adolescent students in government and private schools of Quetta. Moreover, the study also explored the relationship between students’ academic self-concept and self-esteem. The sample comprised 414 students aged 14 - 17 years from government and private schools. Rosenberg’s scale of self-esteem and Academic Self Concept Scale for Adolescents (ASCA) were employed as measures of self-esteem and academic self concept. Results showed that students of government schools scored higher on academic self-concept and students of private schools scored higher on self-esteem. A weak negative correlation was found between academic self-concept and self-esteem. The study recommends developing policies on institutional as well as government level that help incorporate academic self concept into self esteem and self concept of students.